Strong static and dynamic Jahn-Teller and pseudo-Jahn-Teller effects in niobium tetrafluoride - Vasilyev, Oleg A.; Nandipati, Krishna Reddy; Navarkin, Ilya S.; Solomonik, Victor G.; Domcke, Wolfgang (The journal of chemical physics, 2021)
We present a first-principles study of the static and dynamic aspects of the strong Jahn-Teller (JT) and pseudo-JT (PJT) effects in niobium tetrafluoride, NbF4, in the manifold of its electronic ground state, 2E, and its first excited state, 2T2. The complex topography of the full-dimensional multi-sheeted adiabatic JT/PJT surfaces is analyzed computationally at the complete-active-space self-consistent-field (CASSCF) and multireference second-order perturbation levels of electronic structure theory, providing a detailed characterization of minima, saddle points, and minimum-energy conical intersection points. The calculations reveal that the tetrahedral (Td) configuration of NbF4 undergoes strong JT distortions along the bending mode of e symmetry, yielding tetragonal molecular structures of D2d symmetry with Td → D2d stabilization energies of about 2000 cm−1
Gesehen am 21.07.2021